2013
DOI: 10.1038/nnano.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of luminescent excitons in layered nanomaterials

Abstract: In nanomaterials, optical anisotropies reveal a fundamental relationship between structural and optical properties. Directional optical properties can be exploited to enhance the performance of optoelectronic devices, optomechanical actuators and metamaterials. In layered materials, optical anisotropies may result from in-plane and out-of-plane dipoles associated with intra- and interlayer excitations, respectively. Here, we resolve the orientation of luminescent excitons and isolate photoluminescence signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
328
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(352 citation statements)
references
References 35 publications
14
328
2
2
Order By: Relevance
“…An additional pair of TiO 2 /SiO 2 (14 nm/16 nm) is deposited on top of the photonic crystal in order to adapt the BSW energy dispersion to the excitonic transition of the MoS 2 mono-and bi-layer. The MoS 2 transition dipole moment (of the lowest energy excited state) lies in the plane of the device [37], therefore the MoS 2 emitted photons experience the best coupling when using a TE-polarized BSW, as in the case under our investigation.…”
Section: Coupling Mos 2 Mono-and Bi-layer Emissionmentioning
confidence: 63%
“…An additional pair of TiO 2 /SiO 2 (14 nm/16 nm) is deposited on top of the photonic crystal in order to adapt the BSW energy dispersion to the excitonic transition of the MoS 2 mono-and bi-layer. The MoS 2 transition dipole moment (of the lowest energy excited state) lies in the plane of the device [37], therefore the MoS 2 emitted photons experience the best coupling when using a TE-polarized BSW, as in the case under our investigation.…”
Section: Coupling Mos 2 Mono-and Bi-layer Emissionmentioning
confidence: 63%
“…It has been demonstrated that the PL from 2D MoS 2 originates solely from in-plane excitons [46]. Therefore, the PL emission of MoS 2 layers can be described by an isotropic distribution of incoherently radiating dipoles lying in planes parallel to the layer interfaces.…”
Section: And Graphenementioning
confidence: 99%
“…Also of interest are excitons in coupled multi-layer materials [109]. Biexciton binding energy, homogeneous linewidth, and coupling between excitonic species in layered GaSe [110], and exciton dephasing in layered InSe [111], have been recently measured using MDCS by Dey et al…”
Section: Layered Semiconductorsmentioning
confidence: 99%